Netnographic Study of Online Gender-Based Violence (KBGO) on Twitter - Rita Lismini (Jurnal Syntax Admiration, 2023)
This study aims to determine online gender-based violence in the form of online sexual harassment (Cyber Sexual Harassment) that occurs on Twitter. This research uses CMC (Computer-Mediated Communication) theory, and the type of research used is qualitative research using ethnographic methods. The results of this study show that there are six categories of cyber sexual harassment, the first is a direct threat of sexual or physical violence which is any effort, either physical or verbal that leads to a person's sexuality or sexual organs without obtaining consent and has elements or threats. Second, online harassment is an act of sexual harassment through unwanted messages, attention, and contact or intended to embarrass the victim. Third, abusive comments are negative words and without censorship can even be read or may be shared by others.